Estrategias lúdicas para fortalecer el lenguaje oral en los niños de 4 a 5 años de la Unidad Educativa “Hispanoamérica” de la ciudad de Riobamba, período 2021 - Sotamba Bernal, Lorena Elizabeth (2024)
The present research was carried out in the "Hispanoamérica" Primary School of Riobamba City; its main objective was to implement playful strategies to strengthen oral language in children aged 4 to 5 years. Using a qualitative approach since it allowed us to know experiences and emotions where children's language will significantly influence their learning. It was descriptive because it was possible to describe the playful strategies to strengthen oral language through it. It was a field investigation because it was carried out at the scene of the events. The population was eight children, so taking any samples was unnecessary; the observation sheet, which contained ten items for children's observation, was used as an instrument. The same one allowed us to know that there is a language deficit in 40% of children, so we created playful strategies that the teacher uses to improve the children's oral language, giving them confidence and security in their communication.